Interactions between Temperament, Stress, and Immune Function in Cattle - N. C. Burdick; R. D. Randel; J. A. Carroll; T. H. Welsh (International Journal of Zoology)
The detrimental effects caused by stressors encountered by animals during routine handling can pose economic problems for the livestock industry due to increased costs ultimately borne by the producer and the consumer. Stress adversely affects key physiological processes of the reproductive and immune systems. In recent years stress responsiveness has been associated with cattle behavior, specifically temperament. Cattle with more excitable temperaments, as measured by chute score, pen score, and exit velocity (flight speed), exhibit greater basal concentrations of glucocorticoids and catecholamines. Similar to stressed cattle, more temperamental cattle (i.e., cattle exhibiting greater exit velocity or pen and chute scores) have poorer growth performance, carcass characteristics, and immune responses. Thus, understanding the interrelationship of stress and temperament can help in the development of selection and management practices that reduce the negative influence of temperament on growth and productivity of cattle. This paper discusses the relationship between stress and temperament and the developing evidence of an effect of temperament on immune function of cattle that have been handled or restrained. Specifically, the paper discusses different methodologies used to measure temperament, including chute score, pen score, and exit velocity, and discusses the reaction of cattle to different stressors including handling and restraint.